2009
DOI: 10.1002/itdj.20123
|View full text |Cite
|
Sign up to set email alerts
|

Challenges of interorganizational collaboration for information technology adoption: Insights from a governmental financial decision-making process in Egypt

Abstract: This article demonstrates the importance of collaboration between government departments as a backbone for interorganizational integration between agencies. It argues that the challenges related to information technology adoption in developing countries can be partially attributed to the lack of standard collaboration practices between government agencies. A case of a foreign financing decision-making process in Egypt was used as an example of a government process in which there was close collaboration between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…This might explain the dropping of variable 29 as Egyptian society and its companies as of yet do not have much experience with the advantages of diversity. In the case of variable 30 there was some research done in a governmental setting where the results showed that there was a lack of standard collaboration practices between government agencies (Ezz et al, 2004). It might be that this lack is also experienced in a profit setting which might mean that true collaboration, in an HPO sense, is still in its infancy in Egypt.…”
Section: Ijoem 114mentioning
confidence: 99%
“…This might explain the dropping of variable 29 as Egyptian society and its companies as of yet do not have much experience with the advantages of diversity. In the case of variable 30 there was some research done in a governmental setting where the results showed that there was a lack of standard collaboration practices between government agencies (Ezz et al, 2004). It might be that this lack is also experienced in a profit setting which might mean that true collaboration, in an HPO sense, is still in its infancy in Egypt.…”
Section: Ijoem 114mentioning
confidence: 99%
“…In terms of intraorganizational variables, the decision-making related to e-government issues remains centralized in the upper level management through a top-down approach. Unlike previous studies arguing that the degree of centralization influences the acceleration of e-government adoption (Budding et al ., 2018; Ezz et al ., 2009; Waller and Genius, 2015), the present study highlights the importance of decision-making decentralization in e-government projects. Our respondents stressed the importance of being able to make decisions in an agile context, wherein a rigid hierarchy can instead undermine input from personnel who often have a good understanding of operational issues; such hierarchy can also decelerate the e-government adoption process.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, according to Javidan et al (2006), the rewards of employing diversity are not sufficiently appreciated in Egyptian society in general and in businesses specifically, as compared to gender-egalitarian societies. An explanation for the elimination of QE4 can be found in the work of Ezz et al (2009), which revealed the general lack of sufficient collaboration practices by Egyptian organizations.…”
Section: Employee Qualitymentioning
confidence: 99%